Sanchez and friends : Live at London's Hammersmith Apollo (London : Jet Star Phonographics Limited, 2005)
DVD of live performances of Sanchez and his friends in London. Includes performances by George Nooks, Lukie D, Vivian Jones, Don Richardo and Governor Tiggy.
One hundred and fifty-eight (158) minutes.
A special edition for Jamaican independence.
Director and Editor, Roger Zionani ; Producer, Forever Fame Productions ; Executive Producers, A. Linton, M. Ashley, T. Ashley and E. Blackwood.
NLJCols20082021
Keywords: Reggae music; Concert films; Concerts; Concert films; Concerts; Reggae music